Optimization of Cassava Production Management using Fuzzy Logic to Enhance Efficiency and Production Yield - Iklima Istiqomah; Hafiz Agi Alfasih; Herti Herti; Revanda Arifia; Fauzan Naufal Gibran; Angga Eben Ezer; Sesar Husen Santosa; Muhammad Danang Mukti Darmawan; Nanda Octavia (Batrisya Education, 2024)
This research aims to optimize cassava production using fuzzy logic to enhance efficiency and productivity. Cassava is an important agricultural crop in Indonesia with great potential due to its ability to thrive in various types of soil and climates. Despite being considered a secondary food, cassava has numerous health benefits and serves as a good source of energy. However, crop failures and low yields hinder cassava production. Farmers can achieve optimal yields by maximizing output with minimal input costs. In addition to meeting market demand, pricing strategies are also crucial in determining the best products. Therefore, manufacturing companies need to plan the quantity of products to meet the expected demand. Factors such as product supply and demand need to be considered. It is challenging to monitor production elements when manual calculations are used. Hence, a method to accurately predict product availability is needed. The method used is fuzzy logic computation. We employ the Mamdani fuzzy logic method in this study. The outcome of this research is the ability to enhance cassava production yields based on Mamdani fuzzy logic calculations. The computations conducted enable farmers to determine production levels based on consumer demand.